Sustainability in Brazilian floriculture: introductory notes to a systemic approach - Junqueira, Antonio Hélio; Peetz, Marcia da Silva (Ornamental Horticulture, 2018)
The article aims at an introductory exploration of the theme of sustainability in Brazilian floriculture, both in its segment of cut flowers and foliage and in landscaping. The study is based on bibliographic review, data collection and interpretation on the recent performance of the flower and ornamental plants market in Brazil, with emphasis on the role played by the importation of genetic material from exotic species to support commercial activity in the country. From this phenomenon and the productive and distributive concentration of the flowers and plants in the State of Sao Paulo (Holambra, Santo Antônio de Posse, Campinas, Atibaia and Mogi das Cruzes), discusses the national homogenization of taste and consumption habits and requirements for adapting exotic species. In the end, the research points to future ways of investigating the potential of native species exploration in favor of better results for the environmental and socioeconomic sustainability of the floriculture and ornamental plants sector in Brazil.